2013
DOI: 10.3945/jn.112.169672
|View full text |Cite
|
Sign up to set email alerts
|

A Diet High in Resistant Starch Modulates Microbiota Composition, SCFA Concentrations, and Gene Expression in Pig Intestine

Abstract: Resistant starch (RS) is highly fermentable by microbiota in the colon, resulting in the production of SCFAs. RS is thought to mediate a large proportion of its health benefits, including increased satiety, through the actions of SCFAs. The aim of this study was to investigate the effects of a diet high in RS on luminal microbiota composition, luminal SCFA concentrations, and the expression of host genes involved in SCFA uptake, SCFA signaling, and satiety regulation in mucosal tissue obtained from small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
258
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(289 citation statements)
references
References 61 publications
20
258
5
6
Order By: Relevance
“…Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57]. Concordantly to the other studies [16,55,56], the Ruminococcus genus (including R. bromii ) increased in relative abundance in growing pigs that were fed with a type 3 resistant starch-containing diet [30]. An alteration in gut microbiome and a predominance of beneficial bacterial populations were observed in these pigs compared to control pigs.…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57]. Concordantly to the other studies [16,55,56], the Ruminococcus genus (including R. bromii ) increased in relative abundance in growing pigs that were fed with a type 3 resistant starch-containing diet [30]. An alteration in gut microbiome and a predominance of beneficial bacterial populations were observed in these pigs compared to control pigs.…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 72%
“…bromii , E. rectale and Roseburia spp. populations in the gut of different animal models and humans [16,55,56]. Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57].…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 99%
“…The analysis of faecal microbiota was carried out using a phylogenetic microarray comprehensively targeting pig GI tract microbiota, the so-called Pig Intestinal Tract Chip (PITChip), developed by Pérez Gutiérrez (2010) and successfully applied by Haenen et al (2013). The updated version of the PITChip (V2.0) used in this study contained over 3300 oligonucleotides targeting 782 bacterial phylotypes reported to occur in the porcine gastrointestinal tract.…”
Section: Microbial Composition Profilingmentioning
confidence: 99%
“…Faecal microbiota composition was assessed using the Pig Intestinal Tract Chip (PITChip; Pérez Gutiérrez, 2010;Haenen et al 2013), and activity was evaluated using in vitro gas production kinetics and fermentation end-product profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pigs are unable to produce endogenous enzyme for Resistant Search (RS) and thus seek helps from intestinal microbiota which convert it to short chain fatty acid. Haenen et al (2013) stated that diet with high RS modulate the microbial composition in colon and caecal which stimulate the expression of monocarboxylate transporter 1 (SLC16A1) and glucagon (GCG). Feeding strategy is one of the most important factor that control the quality of meat, safety and nutritional value.…”
Section: Application Of Nutrigenomics In Animal Sectormentioning
confidence: 99%